The Therapeutic Effects of Adipose-Derived Stem Cells and Recombinant Peptide Pieces on Mouse Model of DSS Colitis. Issue 9 (September 2018) - Iwazawa, Reiko; Kozakai, Sayako; Kitahashi, Tsukasa; Nakamura, Kentaro; Hata, Ken-ichiro
Cell therapies using adipose-derived stem cells (ADSCs) have been used to treat inflammatory bowel disease (IBD) in human and dog. We previously reported the CellSaic technique, which uses a recombinant scaffold to enhance the efficacy of cell therapy. To examine whether this technique can be applied to cell therapy for colitis, we evaluated the efficacy of CellSaic in colitis mouse models. Colitis mouse models were developed by administering dextran sulfate sodium (DSS) to C57BL/6 mice for 7 days. Then CellSaic comprising human/canine ADSCs (1.2 × 10 6 cells) or human/canine ADSCs only (1.2 × 10 6 cells) were administered to the mice. The body weights were measured, and the colon length measurements and histological evaluations were conducted at 7 days after administration. After in vitro culture of human ADSC (hADSC) CellSaic and hADSC spheroids in medium containing TNFα, the levels of the anti-inflammatory protein TSG-6 in each supernatant were measured. Furthermore, we conducted tumorigenicity and general toxicity tests of canine ADSC (cADSC) CellSaic in NOG mice for 8 weeks. In the colitis mouse models, the ADSC CellSaic group presented recovery of body weight and colon length compared with the ADSC-only group. Histological analysis showed that ADSC CellSaic decreased the number of inflammatory cells and repaired ulceration. In vitro, hADSC CellSaic secreted 3.1-fold more TSG-6 than the hADSCs. In addition, tumorigenicity and general toxicity of cADSC CellSaic were not observed. This study suggests that human and canine ADSC CellSaic has a therapeutic effect of colitis in human and dogs.